2017
DOI: 10.1080/00140139.2017.1282628
|View full text |Cite
|
Sign up to set email alerts
|

Visual map and instruction-based bicycle navigation: a comparison of effects on behaviour

Abstract: Cycling with a classic paper map was compared with navigating with a moving map displayed on a smartphone, and with auditory, and visual turn-by-turn route guidance. Spatial skills were found to be related to navigation performance, however only when navigating from a paper or electronic map, not with turn-by-turn (instruction based) navigation. While navigating, 25% of the time cyclists fixated at the devices that present visual information. Navigating from a paper map required most mental effort and both you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous research has primarily focused on developing visual displays for PMV users (Dancu et al, 2014; De Waard et al, 2017). However, the visual navigation system has some drawbacks, such as privacy concerns and distracted driving: anyone nearby can see the PMV's display, and users must keep their eyes on the screen to see the map, which leads to accidents (Poppinga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has primarily focused on developing visual displays for PMV users (Dancu et al, 2014; De Waard et al, 2017). However, the visual navigation system has some drawbacks, such as privacy concerns and distracted driving: anyone nearby can see the PMV's display, and users must keep their eyes on the screen to see the map, which leads to accidents (Poppinga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is often achieved by using auditory [1,12,16,20,36] or tactile [20,25,27,33] cues to convey the navigation instructions. Other modalities include instructions conveyed through light signals inside the helmet [20,34], on an external navigation device [7] or projections in front of the bicycle [5,6]. Most of these navigation systems use TBT navigation, giving information on where to turn at each decision point.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they concluded that almost a third of the surveyed number of people in the future intends to use this mode of transport much more often, and nearly three-thirds would like to own the electric bicycle as an efficient mode of transport. Waard et al [4] investigated the influence on the behavioral change of cyclists when the common map or smartphone navigation is used for orientation. Prateli et al [5] have dealt with improving bicycle mobility in urban areas through ITS technologies.…”
Section: Introductionmentioning
confidence: 99%